Komunikasi Visual Iklan Layanan Masyarakat Dampak Buruk Kesehatan Akibat Karhutla Di Kota Palembang - Dery Dzawil Qodry; Mukhsin Patriansah (VisArt: Jurnal Seni Rupa dan Design, 2023)
Forest and Land Fires (KARHUTLA) often occur almost every year and have become a regular source of ecological disasters such as causing unhealthy air pollution for the community. Palembang City is an area that often experiences smog every year. The negative impacts resulting from forest and land fires are very detrimental to several parties, generally people will have their activities and health disrupted such as disruption to flight schedules, schooling and community activities will be disrupted such as lack of visibility and danger for traffic travel. building the value of public awareness and alertness regarding the negative impacts of KARHUTLA on health, it is necessary to "Design Public Service Advertisements on the Adverse Health Impacts of KARHUTLA in the city of Palembang" so that the community is more independent and brings provisions for health and is ready to anticipate the negative health impacts due to RHUTLA. The design of this Public Service Advertisement aims as a persuasive effort to empower the people of Palembang to increase their preparedness in facing the negative health impacts caused by forest and land fires. This design is expected to maintain health by improving physical, mental and social health in the people of Palembang.